A Background Study on Ant Colony Optimization Metaheuristic and its Application Principles in Resolving Three Combinatorial Optimization Problem. - Sallim, Jamaludin; Wan Hussin, Wan Muhammad Syahrir; Abdullah, Rosni; Abdul Khader, Ahamad Tajudin (2007)

(untitled)
Colony Optimization (ACO) is a metaheuristic that inspired by the behaviour of real ant colonies and can be considered as a one of recent metaheuristic approach that has been proposed. In this paper, we review the approach by ACO metaheuristic in resolving three the combinatorial optimization problems (COPs).